2008
DOI: 10.1007/s11095-008-9663-7
|View full text |Cite
|
Sign up to set email alerts
|

Global Gene Expression Profiling in Cultured Cells Is Strongly Influenced by Treatment with siRNA–Cationic Liposome Complexes

Abstract: Non-specific effects of siRNA-lipoplexes may either enhance, attenuate or even fully mask the desired outcomes of siRNA-based biochemical studies and therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…However, examining the production of certain types of cytokines is not sufficient to guarantee the safety of a systemic siRNA delivery system. To address this issue, gene expression profiling represents a promising approache to understanding the underlying mechanism of host responses by delivery systems, in the form of toxicogenomics studies [46][47][48][49]. However, the response of a host to a systemically administrated non-viral gene vector has not been examined using this approach.…”
Section: Discussionmentioning
confidence: 99%
“…However, examining the production of certain types of cytokines is not sufficient to guarantee the safety of a systemic siRNA delivery system. To address this issue, gene expression profiling represents a promising approache to understanding the underlying mechanism of host responses by delivery systems, in the form of toxicogenomics studies [46][47][48][49]. However, the response of a host to a systemically administrated non-viral gene vector has not been examined using this approach.…”
Section: Discussionmentioning
confidence: 99%
“…The sequence of siRNA against Argonaute2 (siAgo2) was sense: 5′-UGA GGC ACU UAC CAU CCA UTT-3′ and antisense sequence, 5′-AUG GAU GGU AAG UGC CUC ATT-3′ [21]. The sequence of the non-silencing control siRNA (siNS), which was targeting against GFP, was sense: 5′-GGC UAC GUC CAG GAG CGC ATT-3′ and antisense: 5′-UGC GCU CCU GGA CGU AGC CTT-3′ [22].…”
Section: Animals and Tumor Cell Linementioning
confidence: 99%
“…Therefore, non-viral vector systems should overcome these adverse side effects and represent safer and more efficient alternatives with improved bioavailability and reduced cellular toxicity in the clinics (Akhtar et al, 2000;Somia and Verma, 2000;Panyam and Labhasetwar, 2003). It has been shown that cationic polymers and lipid-based transfection reagents could elicit cellular gene expression changes and complexation with siRNA increased these changes (Omidi et al, 2003;Omidi et al, 2005;Fedorov et al, 2006;Hollins et al, 2007;Tagami et al, 2007;Tagami et al, 2008). Beyerle et al analyzed the expression changes of genes related to cytotoxicity, inflammation and oxidative stress in a pathway focused qRT-PCR array system upon treatment with different PEI-PEG copolymers in murine lung epithelial cells (LA-4 cell line) and could show that PEGylated PEI copolymers altered the gene expression profile on cost of upregulation of genes involved in inflammatory and oxidative stress processes while PEI 25 kDa mainly induced genes related to cytotoxicity and apoptosis (Beyerle et al, 2010a).…”
Section: Toxicogenomics Of Pei-based Non-viral Vector Systemsmentioning
confidence: 99%